2007
DOI: 10.1093/toxsci/kfm289
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicogenomic Examination of the Hepatic Effects of PCB126 and TCDD in Immature, Ovariectomized C57BL/6 Mice

Abstract: Polychlorinated biphenyls are persistent environmental pollutants that elicit a wide range of effects in humans and wildlife, mediated by the aryl hydrocarbon receptor. 3,3',4,4',5-pentachlorobiphenyl (PCB126) is the most potent congener with relative effect potencies ranging from 0.0026 to 0.857, and a toxic equivalency factor (TEF) of 0.1 set by an expert panel of the World Health Organization. In this study, the hepatic effects elicited by 300 microg/kg PCB126 were compared with 30 microg/kg 2,3,7,8-tetrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 41 publications
7
38
1
Order By: Relevance
“…In detail, only three bacterial families including Methanosaetaceae , Erysipelotrichaceae , and a group from clostridia were significantly reduced ( p < 0.05) in mice dosed with CO. In our previous studies using sesame oil—a common vehicle (Brown et al 1998; Kopec et al 2008), we observed a response that opposed TCDD in terms of shifting SFB, Firmicutes , and Enterobacteriaceae (Bhaduri 2015; Stedtfeld et al 2017, submitted). For example, compared to the relative abundance 1 day before dosing, Enterobacteriaceae in fecal pellets decreased ~ 10-fold and 300-fold, 3 and 7 days following an initial dose of sesame oil, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…In detail, only three bacterial families including Methanosaetaceae , Erysipelotrichaceae , and a group from clostridia were significantly reduced ( p < 0.05) in mice dosed with CO. In our previous studies using sesame oil—a common vehicle (Brown et al 1998; Kopec et al 2008), we observed a response that opposed TCDD in terms of shifting SFB, Firmicutes , and Enterobacteriaceae (Bhaduri 2015; Stedtfeld et al 2017, submitted). For example, compared to the relative abundance 1 day before dosing, Enterobacteriaceae in fecal pellets decreased ~ 10-fold and 300-fold, 3 and 7 days following an initial dose of sesame oil, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Animal studies were performed as previously described (Boverhof et al, 2005; Kopec et al, 2008). In short, immature female C57BL/6 ovariectomized (ovx) mice (post natal day 25, Charles River Laboratories, Portage, MI) were housed at 23 °C with 30–40% humidity and 12-h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were fed Harlan Teklad 22/5 Rodent Diet 8640 (Madison, WI) ad libitum and had free access to deionized water. Mice were acclimated for 3 days, and then orally gavaged once with 30 µg/kg TCDD (Boverhof et al, 2005), 300 µg/kg PCB126 (Kopec et al, 2008), 90 mg/kg βNF, or sesame oil (vehicle). The PCB126 dose was chosen based on its toxic equivalency factor (TEF) of 0.1, while doses ≥80 mg/kg βNF elicit maximal hydroxylase activity (Boobis et al, 1977).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects on genes of the steroideogenic pathway relate to the deregulation of cholesterol homeostasis. Observed the inhibition of beta-oxidation, indicating impaired lipid metabolism [63][64][65]. Exposures of dibutyl phthalate were examined in male and female F344/N rats and B6C3F1 mice in 13-week feed studies.…”
Section: Toxicogenomics and Clinical Mechanismsmentioning
confidence: 99%